RISK FACTORS AFFECTING OUTCOME OF ELEVATED INTRACRANIAL PRESSURE IN PEDIATRIC PATIENTS WITH SEVERE ENCEPHALITIS (Vietnam Journal of Community Medicine, 2026)
Objective: Acute encephalitis with coma and elevated intracranial pressure (ICP) is a severe condition associated with high mortality. Multiple factors may influence clinical outcomes; therefore, identifying risk factors associated with mortality in children with severe acute encephalitis and coma (Glasgow Coma Scale ≤8) is essential to optimize treatment strategies.Methods: This prospective descriptive study included children aged 1 month to 16 years who were diagnosed with acute encephalitis with coma (GCS ≤8) and underwent intraparenchymal intracranial pressure monitoring. Patients were treated according to the protocol of the National Children’s Hospital, using a goal-directed strategy to control intracranial hypertension based on ICP, cerebral perfusion pressure (CPP), and mean arterial pressure (MAP). Clinical and laboratory variables, PRISM II score, number of failing organs, and complications related to the disease or its treatment were analyzed according to survival or mortality.Results:During the study period, 44 patients met the inclusion criteria, including 19 survivors and 25 non-survivors. Univariate analysis showed that clinical features such as fever, increased muscle tone, and seizures were not associated with outcome (p>0.05). In contrast, a higher PRISM II score, ≥3 organ failures, PaCO₂ >45 mmHg, persistent intracranial hypertension, central diabetes insipidus, and fluid overload >10% were significantly associated with mortality (p45 mmHg remained independent predictors of mortality (p=0.04 and p=0.03, respectively).Conclusion: Persistent intracranial hypertension and hypercapnia (PaCO₂ >45 mmHg) are independent prognostic factors associated with poor outcomes in children with severe acute encephalitis and elevated intracranial pressure. Strict control of ICP and PaCO₂ plays a crucial role in improving outcomes in this patient population.
Keywords: acute encephalitis, ICP, risk factors